Reinforced concrete beam-column joint simulation under reversed cyclic loads using layered-shell elements In SAP2000 - Sthapit, Ronit; Punchet Thammarak; Pennung Warnitchai; Thanakorn Pheeraphan; Computer and Structures Inc. (CSI), USA; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
Beam-column joint is one of the most complex structural components which is still studied till date. The damage to the joint during a major event such as an earthquake can cause the whole structure to collapse. Even though this fact is well known, practicing engineer still model joint as a rigid connection during NLTHA due to restrictions such as analysis time and model complexity. Hence, the need for a simplistic beam-column joint is realized. In this study a numerical model for the beam-column joint is developed using Layered Shell Elements. The developed model is then subjected the reversed cyclic loading as prescribed in the experiment. The comparison of the results and the numerical simulation show good agreement. The layer-shell model was able to capture the failure mechanism which would not be possible with the current practice of rigid joint modelling. The discrepancy between the experiment and the numerical model can be attributed to the assumption made during the modelling such as zero movement at the supports as well as the inadequacy of experimental data such as constitutive stress strain relationship for the materials.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2020
Keywords: Reinforced concrete construction -- Earthquake effects; Structural frames -- Joints; SAP2000 (Computer program)